2014
DOI: 10.1515/commun-2014-0018
|View full text |Cite
|
Sign up to set email alerts
|

Parental mediation of internet use and cultural values across Europe: Investigating the predictive power of the Hofstedian paradigm

Abstract: The EU Kids Online project aims to enhance knowledge of the experiences and practices of European children and their parents regarding online risks and safety. A crucial research effort by the EU Kids Online network has been a survey in 25 European countries which targeted approximately 1,000 children per country. This article applies a cross-cultural values filter to the data that were gathered on parental mediation and the Internet in this survey. Our intention is to test whether Geert Hofstede’s cross-natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Over the years, in addition to research on television, the study of parental mediation has expanded in response to the growing interest and concern over the role of digital media in children's lives. Scholars have amassed literature on how parents interact with children in the context of digital media use (Clark, 2011;Mertens & d'Haenans, 2014;Holloway, Green, & Love, 2014).…”
Section: Parental Mediationmentioning
confidence: 99%
“…Over the years, in addition to research on television, the study of parental mediation has expanded in response to the growing interest and concern over the role of digital media in children's lives. Scholars have amassed literature on how parents interact with children in the context of digital media use (Clark, 2011;Mertens & d'Haenans, 2014;Holloway, Green, & Love, 2014).…”
Section: Parental Mediationmentioning
confidence: 99%
“…Kirwil's (2009) cross-cultural comparison of parental mediation of children's internet use in Europe shows that restrictive rules are preferred by parents from collectivistic childrearing cultures, whereas social co-use is preferred by parents from individualistic childrearing cultures. Mertens and d'Haenens' (2014) analysis of the EU Kids Online data demonstrates that parents in less collectivistic countries are more likely to report greater involvement in active mediation, co-use, and monitoring, as compared to parents in more collectivistic countries. Unlike Kirwil's (2009) findings, however, Mertens and d'Haenens (2014) did not find a significant association between collectivism and restrictive mediation.…”
Section: Examples Of Monitoring Include Parents' Checking Children's ...mentioning
confidence: 99%
“…Mertens and d'Haenens' (2014) analysis of the EU Kids Online data demonstrates that parents in less collectivistic countries are more likely to report greater involvement in active mediation, co-use, and monitoring, as compared to parents in more collectivistic countries. Unlike Kirwil's (2009) findings, however, Mertens and d'Haenens (2014) did not find a significant association between collectivism and restrictive mediation. Regarding parents' media perception, research has demonstrated that parents' views on media do affect their parental mediation practices (e.g., Lee, 2013;Shin, 2017;Warren, Gerke, & Kelly, 2002).…”
Section: Examples Of Monitoring Include Parents' Checking Children's ...mentioning
confidence: 99%
“…In contrast, individuals from societies with high power distance tend to ensure that everyone should have a "defined" place within the social order. Societal power distance is also reflected in parent-adolescent relationships (Mertens & d'Haenens, 2014) and family behaviors (Shoham & Dalakas, 2003). In low power distance societies, parents are less likely to value children's obedience and more likely to seek equality with their children (Guan & Li, 2017).…”
Section: Moderating Roles Of Societal Power Distance and Individualismmentioning
confidence: 99%